Analysis of Business Innovation Strategies of Light Rail Transit (LRT) - Pipit Fitri Rahayu; Agustina Marzuki; Agung Anggoro Seto (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
This research aimed to formulate the business innovation strategy of LRT in Palembang. The type of this research was qualitative descriptive. The population used in this study was all users of the LRT. The sampling technique was accidental sampling with a total number of 200 respondents consisting of the LRT’s users and the local communities. This sample also included 5 informants who served as employees of LRT Palembang. The data were collected from both primary and secondary sources. The data were then processed using a SWOT analysis. The results showed that the analytical value of the internal factors was 2.80, and the analytical value of the external factors was 2.3, meaning that the right business innovation strategies for the LRT were strategies with the nature of Strenght Threat (ST). The forms of innovation strategies that can be developed include conducting service promotion, establishing cooperation with other companies, building connectivity with other modes of transportation through government support, and maximizing infrastructure and facilities to create support services or other business units.